Análisis De La Internacionalización De Una Universidad Pública Estatal A Través De La Movilidad Estudiantil - Divad Dinorah García García; Fabiola de Jesús Mapén Franco; Jorge Alberto Rosas Castro (European Scientific Journal, ESJ, 2017)
Internationalization in higher education is a complex process derived from the new social, cultural, and economic dynamics that was generated in national and international context. It was conceived as a strategy to guarantee society with better job opportunities. It starts with the social relevance of the curriculum and the development of institutional programs that favors it. For Higher Education Institutions (IES) to enter into this dynamic process, Knight (1994) describes the integration of the international and intercultural dimensions in the teaching, research, and service functions of the institution. In this sense, the objective of the present investigation is to study the incursion of the Autonomous Juarez University of Tabasco (UJAT) based on the process of internationalization. This is done by analyzing the statistical information of the institutional program of the mobility of undergraduate students in period 2012-2016. The research approach is qualitative based on the documental analysis of the information contained in the Institutional Development Plans (IDP) 2012-2016 and 2016-2020, as well as in the annual reports of activities included in the study period. Statistics show that each year, the number of students increased with an increase of 69.6% when comparing the first year of the study with the year 2016. In order to determine the results of this study in absolute terms, the total enrollment of the UJAT in undergraduate degree in the years 2012 and 2016 was compared with the number of participating students, resulting in 0.17% and 0.53%, respectively.